2008
DOI: 10.1002/elps.200800089
|View full text |Cite
|
Sign up to set email alerts
|

Separation of multiphosphorylated peptide isomers by CZE

Abstract: A separation of mono, doubly and triply phosphorylated isomers was developed with CZE with an aqueous electrolyte containing 3.9 mol/L formic acid and 30% v/v trifluoroethanol. Thus a mixture of ten phosphopeptides corresponding to the human tau sequence 226-240 was separated within 70 min. Although peptides with different phosphorylation degrees, i.e. 0-3 phosphate groups, were well separated, some of the phosphopeptide isomers containing one or two phosphate groups were only partially separated. The electrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 28 publications
1
15
0
Order By: Relevance
“…As shown in Fig. 3, a full separation of all peptides was achieved in less than 14 min with a satisfactory resolution between P-T231/NP-T231 and P-S262/NP-S262 (4.8 and 8.7, respectively), similar to what was previously reported by Muetzelburg and Hoffmann [30].…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…As shown in Fig. 3, a full separation of all peptides was achieved in less than 14 min with a satisfactory resolution between P-T231/NP-T231 and P-S262/NP-S262 (4.8 and 8.7, respectively), similar to what was previously reported by Muetzelburg and Hoffmann [30].…”
Section: Resultssupporting
confidence: 86%
“…Furthermore, Li et al reported the analysis of phosphoproteins on an integrated glass chip that included a CE separation channel and MS detection [29]. Muetzelburg and Hoffmann have developed recently a CZE method using formic acid as BGE for the analysis of synthetic phosphopeptides related to tau protein [30].Tau is a normal brain phosphoprotein that belongs to the family of microtubule-associated proteins. Hyperphosphorylated forms of tau are the major constituents of the neurofibrillary lesions that are observed in Alzheimer's disease and other tauopathies.…”
mentioning
confidence: 99%
“…Separation of both enantiomers and diastereomers of di‐, tri‐, and tetrapeptides was achieved by CE in 0.5 M acetic acid BGE using diMe‐β‐CD, (+)‐(18‐crown‐6)‐2,3,11,12,‐tetracarboxylic acid, combination of these two compounds, or L‐histidine as chiral selectors 185. Complete or at least partial separation of positional isomers of mono, doubly and triply phosphorylated peptide fragments of human tau protein was achieved by CZE in BGE composed of 3.9 mol/L formic acid and 30% v/v trifluoroethanol 253.…”
Section: Applicationsmentioning
confidence: 99%
“…Therefore, analysis of the change of the phosphorylation of endogenous peptides is valuable for the diagnosis of diseases. However, due to their low abundance and lower ionization efficiency than nonphosphorylated peptides, enrichment method is normally required for phosphopeptides analysis []. Recently, titanium ion‐immobilized mesoporous silica particles have been successfully used to enrich the endogenous phosphopeptides from human serum because of their high adsorption specificity toward phosphopeptides [].…”
Section: Introductionmentioning
confidence: 99%